Physiotherapy in individuals with peripheral arterial occlusive disease – a retrospective study - Perreira, Danielle Aparecida Gomes; Montezzo, Dayane; Costa, Daniela Odete B R; Silva, Fabio Campos; Braga, Marcella Junia; Britto, Raquel Rodrigues (Revista de Fisioterapia Respiratória e CardioVascular, 2012)
Introduction: Treatment for peripheral arterial occlusive disease (PAOD) may consist of intervention procedure, including surgery, and conservative techniques such as rehabilitation. The exercise-based rehabilitation is a viable alternative due to its low cost and effectiveness in functional improvement. Objective: To evaluate results obtained through physiotherapy for individuals with PAOD in an outpatient program for a minimum of three months. Methods: Retrospective observational study where data were gathered through a medical chart survey. Functional capacity was assessed using the shuttle walking test and six-minute walk test and functional capacity was evaluated via the Short-Form Health Survey. Results: Forty medical charts were selected, of which 12 met inclusion criteria. Functional capacity and quality of life measures showed significant improvement. Functional capacity and SF-36 variables were analyzed using the paired t-test. Conclusion: Twice-weekly supervised treatment displayed favorable results in functional capacity and quality of life measures.